Target-agnostic identification of human antibodies to Plasmodium falciparum sexual forms reveals cross-stage recognition of glutamate-rich repeats - Axelle Amen; Randy Yoo; Amanda Fabra-García; Judith Bolscher; William JR Stone; Isabelle Bally; Sebastián Dergan-Dylon; Iga Kucharska; Roos M de Jong; Marloes de Bruijni; Teun Bousema; C Richter King; et al. (eLife)
Circulating sexual stages of Plasmodium falciparum (Pf) can be transmitted from humans to mosquitoes, thereby furthering the spread of malaria in the population. It is well established that antibodies can efficiently block parasite transmission. In search for naturally acquired antibodies targets on sexual stages, we established an efficient method for target-agnostic single B cell activation followed by high-throughput selection of human monoclonal antibodies (mAbs) reactive to sexual stages of Pf in the form of gametes and gametocyte extracts. We isolated mAbs reactive against a range of Pf proteins including well-established targets Pfs48/45 and Pfs230. One mAb, B1E11K, was cross-reactive to various proteins containing glutamate-rich repetitive elements expressed at different stages of the parasite life cycle. A crystal structure of two B1E11K Fab domains in complex with its main antigen, RESA, expressed on asexual blood stages, showed binding of B1E11K to a repeating epitope motif in a head-to-head conformation engaging in affinity-matured homotypic interactions. Thus, this mode of recognition of Pf proteins, previously described only for Pf circumsporozoite protein (PfCSP), extends to other repeats expressed across various stages. The findings augment our understanding of immune-pathogen interactions to repeating elements of the Plasmodium parasite proteome and underscore the potential of the novel mAb identification method used to provide new insights into the natural humoral immune response against Pf.